Investigating the acoustic response of gold nanoparticle coated microbubbles - Mohamedi, G; Rademeyer, P; Azmin, M; Edirisinghe, M; Perez-Juste, J; Pastoriza-Santos, I; Liz-Marzan, L; Stride, E (2013)
Recent work has shown that incorporating solid nanoparticles into the coatings of contrast agent microbubbles can be used to control their stability and to provide other functional characteristics for example in multimodality imaging. The aim of this study was to investigate the influence of nanoparticle characteristics and concentration on the response of the microbubbles to ultrasound excitation. Theoretical models were first derived to simulate the effects of adsorbing different types and concentrations of nanoparticle on to the surface of a bubble in both a monolayer and a layer of finite thickness. The results indicate that the particles modify the symmetry of the microbubble oscillations and enhance their nonlinear character. Experimentally, microbubbles coated with a surfactant and varying concentrations of gold nanoparticles of different sizes and surface properties were produced using either sonication or microfluidics. The attenuation and backscattering coefficients from the bubble suspensions and the scattered response from individual bubbles were measured for a range of frequencies (1-7.5MHz) and pressures (50-500kPa). The nanoparticles were found to enhance the nonlinear character of the bubble response in qualitative agreement with the theoretical results. Both the degree of enhancement and stability of the microbubbles was dependent upon the nanoparticle surface chemistry. © 2013 Acoustical Society of America.